Color three-dimensional imaging based on patterned illumination using a negative pinhole array - Kim, Chang-Soo; Kim, Junyoung; Yoo, Hongki (Optics express, 2021)
Reflectance confocal microscopy is widely used for non-destructive optical three-dimensional (3D) imaging. In confocal microscopy, a stack of sequential two-dimensional (2D) images with respect to the axial position is typically needed to reconstruct a 3D image. As a result, in conventional confocal microscopy, acquisition speed is often limited by the rate of mechanical scanning in both the transverse and axial directions. We previously reported a high-speed parallel confocal detection method using a pinhole array for color 3D imaging without any mechanical scanners. Here, we report a high-speed color 3D imaging method based on patterned illumination employing a negative pinhole array, whose optical characteristics are the reverse of the conventional pinhole array for transmitting light. The negative pinhole array solves the inherent limitation of a conventional pinhole array, i.e., low transmittance, meaning brighter color images with abundant color information can be acquired. We also propose a 3D image processing algorithm based on the 2D cross-correlation between the acquired image and filtering masks, to produce an axial response. By using four-different filtering masks, we were able to increase the sampling points in calculation of height and enhance the lateral resolution of the color acquisition by a factor of four. The feasibility of high-speed non-contact color 3D measurement with the improved lateral resolution and brightness provided by the negative pinhole array was demonstrated by imaging various specimens. We anticipate that this high-speed color 3D measurement technology with negative pinhole array will be a useful tool in a variety of fields where rapid and accurate non-contact measurement are required, such as industrial inspection and dental scanning.